Economic feasibility analysis of agribusiness sub terminal in integrated agricultural program area - Wawan Tolinggi; Amelia Murtisari; Yanti Saleh; Ahmad Fadhly (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
Agribusiness sub terminal development intends to enable the commodity handling system of the agricultural products covered by one agribusiness management. In addition, farmers and related stakeholders can gain benefits from the development of creating mutual prosperity. This research aims at; 1) analysing the feasibility of agribusiness subterminal in integrated agriculture program area based on financial non-financial aspects, such as market, organizational management, technical operation, and social economy including technical side of agribusiness sub terminal; and 2) generating a policy in supporting the establishment of agribusiness subterminal in integrated agriculture program area in Bone Bolango regency. This descriptive quantitative and qualitative research employs mix method, which consists of exponential comparison method, to determine the technical feasibility of agribusiness subterminal in the integrated agriculture area in Bone Bolango regency. The results reveal that: (1) based on the technique of location determination exponential comparison method, decent sub-districts for the development of agribusiness sub terminal, in sequence, are Tapa, Suwawa, Kabila, and Tilongkabila; (2) From the analysis of economic feasibility of agribusiness sub terminal, Bone Bolango regency shows its worthiness and therefore has potential to advance further; (3) The most potential site is Tapa district; (4) Based on the financial feasibility, specifically the economic aspect, the prospect of, implementing agribusiness sub terminal is high in Bone Bolango regency. Keywords: Agribusiness Sub Terminal, Feasibility, Policy